Protective effects of Liuweiwuling tablets on carbon tetrachloride-induced hepatic fibrosis in rats - Huimin Liu; Zhenfang Zhang; Huangwanyin Hu; Congen Zhang; Ming Niu; Ruishen Li; Jiabo Wang; Zhaofang Bai; Xiaohe Xiao (BMC, 2018)
Abstract Background Liuweiwuling tablets (LWWL) are an herbal product that exerts remarkable effects on liver protection and aminotransferase levels, and they have been approved by the Chinese State Food and Drug Administration (CFDA). Clinical studies have found that LWWL can inhibit collagen production and reduce the levels of liver fibrosis markers in the serum. Thus, LWWL is expected to have beneficial effects in the treatment of liver fibrosis. The purpose of this study was to evaluate the pharmacological effects of LWWL. Methods Hepatic fibrosis was induced in rats via carbon tetrachloride (CCl4) treatment. The rats were treated twice weekly for 8 weeks with either 2 mL·kg− 1 body weight of a 50% solution of CCl4 in olive oil or olive oil alone by oral gavage. A subset of rats received daily intraperitoneal injections of either colchicine (0.2 mg/kg per day), LWWL (0.4, 1.6, or 6.4 g/kg per day), or vehicle (N = 12 for all groups) during weeks 9-12. The rats were sacrificed after 12 weeks. Pathological changes in hepatic tissue were examined using hematoxylin and eosin (H&E) and Sirius Red staining. Immunohistochemistry was performed to observe α-smooth muscle actin (α-SMA) and collagen type I (collagen I) protein expression. Western blotting was also used to detect α-SMA protein expression. Real-time quantitative reverse-transcription polymerase chain reaction (RT-qPCR) was used to detect transforming growth factor-1 (TGF-β1), platelet-derived growth factor (PDGF), tissue inhibitor of metalloproteinase-1 (TIMP1), and tissue inhibitor of metalloproteinase-2 (TIMP2) mRNA expression. Results LWWL significantly reversed histological fibrosis and liver injury, reduced the hydroxyproline content in liver tissue, and decreased α-SMA and collagen I expression. LWWL also suppressed hepatic stellate cell (HSC) activation by reducing the expression of the profibrogenic factors TGF-β1 and PDGF. The expression levels of TIMP1 and TIMP2, which regulate extracellular matrix (ECM) degradation, were decreased after CCl4 injury in LWWL-treated rats. Conclusions These data suggest that LWWL may serve as a promising therapeutic agent to reduce fibrogenesis.